Material Ecstasy: cultural alienation and the influence of the nouveau roman in the work of Nakahira Takuma and J.M.G. Le Clézio. (4th May 2021) - Matheson, Neil
Abstract : This article analyses some of the important early work (ca. late 1960s-early 1970s) of the Japanese photographer Nakahira Takuma (1938–2015) in terms of the themes of materiality and cultural alienation, focusing on Nakahira's links with radical European art and writing of the period. In particular, it explores the relationship with the work of the French writer J.M.G Le Clézio in early writings such as Le Procès-Verbal (1963), L'Extase matérielle (1967) and La Guerre (1970). Le Clézio includes a selection of his own photos as an appendix to La Guerre and the article also embraces an analysis of that imagery and its role in relation to the author's association with the nouveau roman during this early, experimental phase of his career.